2016
DOI: 10.1016/j.landusepol.2016.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Are Malaysians eager to use their cars less? Forecasting mode choice behaviors under new policies

Abstract: a b s t r a c tIn Malaysia, transportation accounts for almost 70% of carbon monoxide emissions. This study sought to discover whether intelligently changing policies for the private and public transport sectors can affect mode choice of private car owners in the Klang Valley, Malaysia. Results of a random parameter logit model identified the most significant parameters affecting respondents' utility measures. These were introducing a congestion fee in private transport mode; and also access, comfort and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Individual-specific factors are associated with the travelers' demographic and socioeconomic attributes, which include age, gender, educational level, occupation, employability, household size, monthly income, lifestyles, and social activities [42][43][44]. The involvement of monetary crises has demonstrated that adjustments in the travel patterns contrast in connection to the family income, the distance, and the mode choices.…”
Section: Influencing Factors Mode Choicementioning
confidence: 99%
“…Individual-specific factors are associated with the travelers' demographic and socioeconomic attributes, which include age, gender, educational level, occupation, employability, household size, monthly income, lifestyles, and social activities [42][43][44]. The involvement of monetary crises has demonstrated that adjustments in the travel patterns contrast in connection to the family income, the distance, and the mode choices.…”
Section: Influencing Factors Mode Choicementioning
confidence: 99%
“…Users would be less likely to choose transport modes with longer commute times [16]. The perception of the commute time is more sensitive to the bus mode (i.e., a shorter or longer trip can influence bus use more than the other modes) [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Users' interest in switching to a more efficient public transport mode grows as the commute time and costs for private transport increase [17].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…2.6 Road traffic policies/regulations Kaffashi et al (2016) asserted that Malaysians are eager to minimize their car usage if innovative transport policy is implemented. Policies, such as proper pricing and efficient public transport, could shift the mode of transport from personal vehicles to public transport to the extent of 70 percent.…”
Section: Intention To Follow Road Disciplinementioning
confidence: 99%